Determinants of Outpatient Satisfaction Based on Health Service Quality Dimensions in Primary Health Care - Wahyu Ratri Sukmaningsih; Wahyu Wijaya Widiyanto; Meldha Ayu Subekti; Joaquim Gregório de Carvalho (Jurnal Infokes, 2026)
Primary health care performance is closely linked to patient satisfaction, which reflects the extent to which services meet patient expectations. This study aimed to identify the determinants of outpatient satisfaction based on health service quality dimensions at Puskesmas Simo, Boyolali. A cross-sectional analytical observational design was applied involving 100 outpatient respondents selected through convenience sampling. Data were collected using a validated and reliable structured questionnaire and analyzed using univariate, bivariate, and multivariate logistic regression methods. Results showed that the majority of respondents rated service quality positively across all SERVQUAL dimensions, with 90% reporting satisfaction. Multivariate analysis revealed that four dimensions of reliability (OR = 6,08), responsiveness (OR = 4,20), assurance (OR = 2,66), and empathy (OR = 5,09) significantly influenced outpatient satisfaction (p < 0,05), whereas tangibles did not (p = 0,220). Reliability was the strongest determinant, indicating that patients perceiving consistent, timely, and accurate services were more than six times likely to report satisfaction. These findings highlight that non-physical aspects of service quality, including interpersonal interactions and service process effectiveness, are more decisive than physical infrastructure in determining patient satisfaction. Strengthening staff competencies, ensuring standardized procedures, and promoting patient-centered care are recommended to enhance service quality in primary health care.